Financial convergence in the Asia Pacific economies - Ibrahim, Juliana; Habibullah, Muzafar Shah (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2013)
Asia Pacific Economic Cooperation (APEC) is an example of a regionalism with aims to improve quality of growth and strengthen regional economic integration through free and open trade and investment. The purpose of this study is to investigate how far have Malaysia performed from its financial development perspective compared to the other member countries and simultaneously address the issue whether the formation of APEC as an economic cooperation has been successful or remains heterogeneous. By applying annual panel data, the hierarchical cluster results suggest the existence of convergence clubs among the Asia Pacific countries. Malaysia is found to be converging towards richer countries’ convergence club. In this respect, in order for the national leaders to continue with strong commitment to support financial development with a shared commitment to the Asian regionalism, the countries with relatively under-developed financial system are expected to relieve their existing credit constraints. Meanwhile, the challenge for Malaysia and other countries with relatively well-developed financial system lie in making their financial services more available to the region over the coming years.